New Triterpenoids from Peucedanum ruthenicum: Triterpenoids from Peucedanum ruthenicum - Marzieh Matin Yekta; Seyed Hamid Reza Alavi (Iranian Journal of Pharmaceutical Sciences, 2008)
From hexanic extract of aerial parts of Peucedanum ruthenicumM. Bieb (Apiaceae) collected from Mazandaran province of Iran, four triterpenoids namely taraxasterol, y-taraxasterol, poriferasterol and b-sitosterol have been isolated by column chromatography, thin layer chromatography, and crystallization. Their structures were elucidated by spectroscopic methods (UV, IR, MS, 1Hand13C-NMR).